Prophetic Philosophy of Mykola Berdyaev as the Art of Understanding in the Context of Global Crisis - Gorban, Richard (Journal of religious and theological information, 2021)
This article is an in-depth study of the prophetic philosophy of Berdyaev as it related to the threat of totalitarianism as a response to the current global pandemic. The author considers Berdyaev’s conceptual interpretation of prophetic philosophy as a special way of philosophical and religious understanding of the world and humanty, based on the religious studies and philosophy of art for the first time. The defining theoretical and methodological provisions of this study are the conceptual orientation toward the complementarity of ideographic and biographical methods, specific to humanitarian knowledge, which made it possible to reveal the genesis of the formation of the theoretical foundations of Berdyaev’s concept of prophetic philosophy and implementation of these principles in Berdyaev’s creative thinking.